UPAYA MENUMBUHKAN KEMAMPUAN MEMBANGUN WEBLOG PRIBADI DIKALANGAN REMAJA UNTUK KEBUTUHAN KEWIRAUSAHAAN - Malabay, Malabay (Lembaga Penerbitan Universitas Esa Unggul, 2017)
An identical adult era with digital marketing that adjusts for significant and ever-increasing employment. The effect of education on work productivity and income, is one solution that creates innovative and creative employment, how to grow the ability of it ?, how to respond to the era of digitalization and its existence in the all-touch situation on an electronic screen? Adjusting to this problem stripping is classified at the core parts of a weblog and entrepreneurial understanding as well as several factors that influence the success or failure of such a spirit or the effort to cultivate a skill or ability to build and or develop the entrepreneurship for the interests and needs of a person or youth based on electronics, which originated from the independence of the construction of a weblog.Ã‚Â Keywords: weblog, youth, entrepreneurship